The Effect of Thixotropic Additive on the Properties of the G Class Cement - Mustamina Maulani (Penerbitan Universitas Trisakti, 2020)
In oil, gas, and geothermal drilling activities, the casing cementing process is always carried out in order to fulfill its function properly and safely. Therefore, everything that supports these activities must be carefully thought out. Before the actual cementing process is applied in the oil, gas, and geothermal field, laboratory-scale simulation must first be carried out by conducting experiments and testing several formulations of cement, water mixture, and additives to be used. The author chooses thixotropic additives, besides functioning as an accelerator, thixotropic can also strengthen the cement itself. With a number of experiments, an optimal cement slurry composition formulation will be obtained, in the sense that by using as few additives as possible, the requirements of the physical characteristics will meet the required standards for conditions (temperature and pressure) of the formation in the well to be cemented. All cementing activities are expected to run well, smoothly, and on time.